KONTROL POSISI PUTARAN MOTOR DC MENGGUNAKAN ARDUINO DAN PID - Adhitiya Satiawan Suryadata; Agus Halim; Rosehan Rosehan (Program Studi Teknik Mesin Universitas Tarumanagara, 2022)
The development of industrial technology is growing rapidly, especially in the field of control systems, one of the controllers that is often used, namely PID which is composed of proportional, integrals, and derivatives, each control has a different role and to determine the value of each control sometimes trials are needed to find the right value. The advantages of this type of controller are that the algorithm used is simple but with accurate output, in this study a potentiometer is used for determining the set point and then an encoder which is useful for reading DC motor rotation and arduino.uno as a medium in implementing the PID system. This journal aims to be a learning medium to determine the parameters on the PID. The method used is a systematic method that starts with making a literature study that will determine the detailed requirements. After that, it is continued with the design of the microcontroller circuit using the Tinkercad website and doing 2D and 3D designs. The results of the design obtained that this circuit can work perfectly because every input given by the potentiometer can drive the motor smoothly and accurately through the encoder reading.